Training predictor variables of faster marathon time in elite-amateur female marathon runners - Lyubushkina, A. V.; Bezuglov, E. N.; Lazarev, A. M. (Theory and Practice of Physical Culture, 2021)
Objective of the study was to collect a profile of elite-amateur female runners, who are able to run sub-3-hour marathon (S3HM) including their anthropometrical parameters, training regimes, and best non-marathon race performance and to detect predictor variables of faster marathon time.